2022
DOI: 10.1021/acsami.2c09985
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Organo-Fluoro-Rich Anode Electrolyte Interface and Partially Sodiated Hard Carbon Anode for Improved Cycle Life and Practical Sodium-Ion Batteries

Abstract: In this work, a strategy is introduced wherein without keeping any excess cathode, a practical full-cell sodium-ion battery has been demonstrated by utilizing a hard carbon (HC) anode and sodium vanadium fluorophosphate and carbon nanotube composite (NVPF@C@CNT) cathode. A thin, robust, and durable solid electrolyte interface (SEI) is created on the surface of HC through its incubation wetted with a fluoroethylene carbonate (FEC)-rich warm electrolyte in direct contact with Na metal. During the incubation, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 38 publications
(82 reference statements)
1
2
0
Order By: Relevance
“…A clear increase in S a values was observed when the HC composite electrodes were cycled with FEC added to the electrolyte (404.6 � 67.6 nm). We associate this with the formation of a more inhomogeneous SEI layer [82] formed on the HC particle surface, as e. g. reported in 1 M NaClO 4 in EC/ PC(1 : 1). S a analyses were also carried out for calendared spraycoated and DB-coated HC composite electrodes and the corresponding S a values are shown in Figure S13b.…”
Section: Morphological and Structural Characterization Of The Sprayco...supporting
confidence: 79%
“…A clear increase in S a values was observed when the HC composite electrodes were cycled with FEC added to the electrolyte (404.6 � 67.6 nm). We associate this with the formation of a more inhomogeneous SEI layer [82] formed on the HC particle surface, as e. g. reported in 1 M NaClO 4 in EC/ PC(1 : 1). S a analyses were also carried out for calendared spraycoated and DB-coated HC composite electrodes and the corresponding S a values are shown in Figure S13b.…”
Section: Morphological and Structural Characterization Of The Sprayco...supporting
confidence: 79%
“…These stable interfaces ensure the high coulombic efficiency and long-cycle stability of the hard carbon negative electrode, with a capacity of 247.9 mAh g −1 after 500 cycles and a capacity retention rate of 94.8%. Lohani et al formed a thin, dense SEI film on the surface of hard carbon by directly contacting hard carbon that was moistened with a vinyl carbonate electrolyte with sodium metal [ 111 ]. During incubation, the hard carbon negative electrode was partially passivated by a thin SEI film.…”
Section: Challenges and Solutions Of Hard Carbonmentioning
confidence: 99%
“…16 It has been observed that defect-rich hard carbon leads to the formation of an uneven and thick SEI with poor mechanical strength due to increased electrolyte consumption, which lowers the cycling stability and reaction kinetics. 17–22 Much research has focused on electrolytes, 23 defect optimization and introducing oxygen functional groups in HC, 24 artificial SEI, 25,26 presodiation, 27 HC/MoS 2 /NC nanocomposites 28 etc. , to obtain a stable, uniform, and thin SEI.…”
Section: Introductionmentioning
confidence: 99%